Documentary Video as a Media for Preserving the Tundukak Tradition in Solok City: A Visual Design Approach to Increase Awareness of Tradition and Symbolic Meaning for the Digital Generation - Sherly Permata Sari Rabbiluski; I Putu Gede Suyoga; I Nyoman Larry Julianto (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
This research discusses the design of a documentary video as a medium for preserving the Tundukak tradition in Solok City, using a visual design approach that involves the digital generation. The Tundukak tradition, as a Minangkabau cultural heritage, contains social, philosophical, and symbolic values ​​that are beginning to shift due to modernization and the lack of understanding among the younger generation. Through qualitative research methods including literature review, interviews with traditional leaders, and field observations, this study produced a documentary video that represents the Tundukak tradition visually, narratively, and symbolically. Semiotic theory, visual ethnography, and documentary video were used as the foundation for constructing the narrative and interpreting the cultural symbols contained within. The results of this design demonstrate that the documentary video can be an effective means of increasing awareness, knowledge, and understanding of the traditional values ​​and symbolic meanings of Tundukak among the digital generation. Furthermore, this work also functions as a visual archive that can support efforts to preserve local culture sustainably amidst the challenges of the globalization era.